Soil physical and hydraulic properties of a toposequence tableland in Bahia State, Brazil - Souza, Luciano da Silva; Ribeiro, Antonio Carlos; Costa, Liovando Marciano da; de Queiroz Paiva, Arlicélio (Pesquisa Agropecuaria Brasileira, 2000)
A study was carried out in Sapeaçu, State of Bahia, Brazil, on a tableland toposequence cultivated with sweet orange 'Hamlin', to determine the soil physical and hydraulic properties. The toposequence consisted of an Argisolic Yellow Latosol, a Yellow Argisol, and a Gray Argisol. For each soil type, one soil profile was studied. Soil samples were collected in each horizon with three replications. These soil samples were analyzed for texture, water clay dispersion, bulk density, particle density, organic carbon, total porosity, macroporosity, microporosity, aggregates analyses, and saturated hydraulic conductivity. The dense horizons of the Argisolic Yellow Latosol and the Yellow Argisol showed the lowest meanweight diameter of aggregates and higher values of microporosity, which result in lower values of saturated hydraulic conductivity. The Gray Argisol presented higher values of macroporosity and saturated hydraulic conductivity.